Digital Economy Taxation in Global Perspective: A Systematic Literature Review and Cross-Country Comparison - Anastasia D'Ornay; Lina Mariana; Sariana Damis; Hernianti Harun; Rusli; Matteo Rossi (Jurnal Riset Perpajakan: Amnesty, 2025)
This study systematically examines the evolution, implementation, and challenges of digital economy taxation across various jurisdictions to provide a comprehensive understanding of global policy trends. Using the PRISMA (2020) framework, a systematic literature review was conducted covering 65 peer-reviewed articles, policy papers, and institutional reports published between 2020 and 2025. The review identifies three dominant themes: (1) the emergence of Digital Services Taxes (DST) and their fiscal implications, (2) the implementation of the OECD/G20 Two-Pillar Solution emphasizing global minimum taxation, and (3) administrative digitalization for tax compliance improvement. A cross-country comparison highlights significant disparities between developed and developing economies in policy adoption, compliance infrastructure, and digital readiness. While OECD member states prioritize the harmonization of tax bases and avoidance of double taxation, developing nations focus on revenue mobilization and fairness in taxing digital activities. The findings reveal that the global minimum tax enhances coordination among multinational enterprises but poses administrative challenges in low-income countries. The study contributes to international taxation discourse by integrating evidence from diverse contexts and proposing a conceptual model linking digital transformation, tax equity, and compliance efficiency. Future research should explore the long-term economic and behavioral impacts of digital tax regimes, especially in the context of global e-commerce and cross-border data monetization.